Green synthesis of biocompatible carboxylic curdlan-capped gold nanoparticles and its interaction with protein. (6th March 2015) - Yan, Jing-Kun; Liu, Jin-Lin; Sun, Yu-Jia; Tang, Shuang; Mo, Zheng-Ying; Liu, Yuan-Shuai
Highlights: A facile, green strategy was developed for the preparation of AuNPs. Use of carboxylic curdlan (Cc) both as reducing and stabilizing agent. The Cc-capped AuNPs with high stability are spherical and well dispersed in solution. Carboxylic groups in Cc molecules tend to absorb and stabilize the surface of AuNPs. The AuNPs can be developed as a potential candidate in biomedicine and biotechnology. Abstract: This study demonstrates a facile, green strategy for the preparation of gold nanoparticles (AuNPs) from chloroauric acid (HAuCl4 ) using carboxylic curdlan (Cc) as both reducing and stabilizing agent. The as-prepared AuNPs are characterized by UV–vis spectroscopy, high resolution transmission electron microscopy, X-ray diffraction, energy dispersive X-ray spectrometry and Fourier transform infrared spectroscopy. The results indicated that the particle size of the AuNPs changes with variations in the reaction time and concentrations of Cc and HAuCl4 . The spherical AuNPs are well dispersed, exhibiting high stability even after six months storage. The carboxylic groups (COO − ) in the Cc molecules tend to adsorb and stabilize the surface of the AuNPs. The interaction between BSA and the Cc-capped AuNPs was investigated using fluorescence and circular dichroism spectroscopies. The results indicated that the BSA molecules adsorb on the surface of the AuNPs, without significant change in its helical structure even after conjugation with the AuNPs.